The Influence of Oregano Essential Oil and Rhus Coriaria L. on Qualitative Parameters and Microbiological Indicators of Hens Eggs Content - Henrieta Arpášová; Miroslava Kačániová; Branislav Gálik; Martin Mellen (Scientific Papers Animal Science and Biotechnologies, 2023)
In this experiment the effects of supplementation of the diet for laying hens with oregano essential oil and Rhus coriaria L. seeds addition on physical and microbiological egg parameters were studied. Hens of laying hybrid Hy-Line Brown (n=30) were randomly divided into 3 groups (n=10) and fed for 20 weeks with diets with oregano essential oil and Rhus coriaria L.seeds supplemented. In the control group hens received feed mixture with no additions. The diets in the first experimental groups were supplemented with 1 ml/kg oregano essential oil. The feed for second experimental group of birds consisted of basal diet supplemented with Rhus coriaria L. seeds (1% in total feed mixture). The results suggest that the most of qualitative parameters of egg internal content and egg shell were not significantly influenced with oregano oil or Rhus coriaria L. seeds addition (p>0.05). A statistically significant difference in favour of the experimental groups compared with the control group was observed in two indicators of albumen quality, in the index of albumen and in the Haugh Units (p<0.05). The highest total number of bacteria and count of coli forms bacteria was found in the control group. The number of lactobacilli was zero in all groups.